The Effect of Fish Oil-Based Lipid Emulsion and Soybean Oil-Based Lipid Emulsion on Cholestasis Associated with Long-Term Parenteral Nutrition in Premature Infants - Leilei Wang; Jing Zhang; Jiejin Gao; Yan Qian; Ya Ling (Gastroenterology Research and Practice)
Purpose. To retrospectively study the effect of fish oil-based lipid emulsion and soybean oil-based lipid emulsion on cholestasis associated with long-term parenteral nutrition in premature infants. Methods. Soybean oil-based lipid emulsion and fish oil-based lipid emulsion had been applied in our neonatology department clinically between 2010 and 2014. There were 61 qualified premature infants included in this study and divided into two groups. Soybean oil group was made up of 32 premature infants, while fish oil group was made up of 29 premature infants. Analysis was made on the gender, feeding intolerance, infection history, birth weight, gestational age, duration of parenteral nutrition, total dosage of amino acid, age at which feeding began, usage of lipid emulsions, and incidence of cholestasis between the two groups. Results. There were no statistical differences in terms of gender, feeding intolerance, infection history, birth weight, gestational age, duration of parenteral nutrition, total dosage of amino acid, and age at which feeding began. Besides, total incidence of cholestasis was 21.3%, and the days of life of occurrence of cholestasis were 53±5.0 days. Incidence of cholestasis had no statistical difference in the two groups. Conclusion. This study did not find the different role of fish oil-based lipid emulsions and soybean oil-based lipid emulsions in cholestasis associated with long-term parenteral nutrition in premature infants.